1986
DOI: 10.1212/wnl.36.6.772
|View full text |Cite
|
Sign up to set email alerts
|

Familial Tourette's syndrome

Abstract: We studied a large Mennonite kindred affected by chronic motor tics (CMTs) and vocal tics in a probable autosomal dominant pattern. We administered a standardized questionnaire to 69 family members and reviewed our videotapes of 47. Using DSM III criteria and independent ratings, we diagnosed 10 subjects as having definite Tourette's syndrome (TS), 3 with definite CMTs, 15 with probable TS, and 1 with probable CMT. The clinical features of this family are presented. This is the largest known kindred with TS. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(25 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…13 We have seen other patients with simple or multiple motor tic disorders (which, in many cases, may be simply a more restricted expression of the Tourette gene 14 ) who experience painful symptoms easily subdivided into one or more of the classes listed in Table 1. Although reason might predict the contrary, in our patient population, pain has been no more common in Tourette patients and in those with multiple-motor tics than in patients with simple motor tics.…”
Section: Discussionmentioning
confidence: 99%
“…13 We have seen other patients with simple or multiple motor tic disorders (which, in many cases, may be simply a more restricted expression of the Tourette gene 14 ) who experience painful symptoms easily subdivided into one or more of the classes listed in Table 1. Although reason might predict the contrary, in our patient population, pain has been no more common in Tourette patients and in those with multiple-motor tics than in patients with simple motor tics.…”
Section: Discussionmentioning
confidence: 99%
“…One of the initial presentations of this condition in the modern literature reported on four children from Alberta, three Hutterites, and one Mennonite [Lowry et al, 1985]. The Mennonite child was a male born to Kurlan et al [1986] non-consanguineous parents and had the typical features of restrictive dermopathy. The authors indicated that the 3 Hutterite patients were potentially descendants of a woman and her 5 children who were amongst 15 ''Mennonites'' who joined the Hutterite brethren in 1783.…”
Section: Methodsmentioning
confidence: 99%
“…While these relatives fultil DSM criteria for I S , they have mild symptomatology, most have never consulted a doctor about their symptoms, they are unknown to medical services and are not on medication (Kurlan et al 1986(Kurlan et al , 1987Caine et al 1988;Hobenson and Gourdie 1990;McMahon et al 1992). The results of this population-based study confirm this protile.…”
Section: Discussionmentioning
confidence: 99%